The Interaction Between Nodal, Hypoxia-Inducible Factor 1 Alpha, and Thrombospondin 1 Promotes Luteolysis in Equine Corpus Luteum - Walewska, Edyta; Wołodko, Karolina; Skarzynski, Dariusz; Ferreira-Dias, Graça; Galvão, António (Frontiers in Endocrinology, 2019)
The regulation of corpus luteus (CL) luteolysis is a complex process involving a myriad of factors. Previously, we have shown the involvement of Nodal in functional luteolysis in mares. Presently, we ask the extent of which Nodal mediation of luteolysis is done through regulation of angioregression. We demonstrated the interaction between Nodal and hypoxia-inducible factor 1 α (HIF1α) and thrombospondin 1/thrombospondin receptor (TSP1/CD36) systems, could mediate angioregression during luteolysis. First, we demonstrated the inhibitory effect of Nodal on the vascular marker platelet/endothelial cell adhesion molecule 1 (CD31). Also, treatment of mid CL explants with vascular endothelial growth factor A (VEGFA) showed a trend on activin-like kinase 7 (Alk7) protein inhibition. Next, Nodal was also shown to activate HIF1α and in vitro culture of mid CL explants under decreased oxygen level promoted Nodal expression and SMAD family member 3 (Smad3) phosphorylation. In another experiment, the crosstalk between Nodal and TSP1/CD36 was investigated. Indeed, Nodal increased the expression of the anti-angiogenic TSP1 and its receptor CD36 in mid CL explants. Finally, the supportive effect of prostaglandin F2α (PGF2α) on TSP1/CD36 was blocked by SB431542 (SB), a pharmacological inhibitor of Nodal signaling. Thus, we evidenced for the first time the in vitro interaction between Nodal and both HIF1α and TSP1 systems, two conserved pathways previously shown to be involved in vascular regression during luteolysis. Considering the given increased expression of Nodal in mid CL and its role on functional luteolysis, the current results suggest the additional involvement of Nodal in angioregression during luteolysis in the mare, particularly in the activation of HIF1α and TSP1/CD36.